Efficacy and landscape of Covid-19 vaccines: a review article - Azevedo,Thomás Cavalcanti Pires de (2021)
SUMMARY INTRODUCTION: The rapid advance of Coronavirus disease 2019 (Covid-19) has led to the incessant search for therapeutic and prophylactic measures to fight the pandemic. Because it is a viral infection, the safest long-term prophylactic form, in addition to social distance and hygiene, is the vaccine. OBJECTIVE: Thus, this study aimed at conducting a review of the efficacy and landscape of Covid-19 vaccines. METHODS: The following electronic databases were used MEDLINE via PubMed, SCIELO, LILACS, NEJM, and Clinical Trials. Our study includes the 7 vaccines (phase 3) that reported an efficacy rate for Covid-19, including characteristics inherent to each one of them. RESULTS: Preliminary studies have shown that, although an efficacy ≥70% is necessary to eliminate the infection, a prophylactic vaccine with efficacy <70% will still have an important impact and can contribute to the elimination of the virus, provided that appropriate measures of social distancing remain. CONCLUSIONS: The effectiveness of the vaccines obtained in this study varied between 50.38 and 95%, data that may represent a reduction in serious cases, hospitalizations, sequels, and deaths caused by Covid-19, respecting the panorama presented in this article.